THE PROFESSIONAL IDENTITY OF THE PEDAGOGUE: FIELD OF ACTIVITY AT SCHOOL AND OUTSIDE OF SCHOOL (REMUNOM, 2026)
Identity is one of the important characteristics of human beings (Dubar, 2006). In the professional field, identity reveals who that professional is and their responsibilities in society. Thus, all initial training involves a professional identity to be formed in graduates. In the case of the pedagogy course, this identity is complex, as it trains for education that manifests itself in diverse spaces and modalities (Libâneo, 2010). For this reason, the following question arose: what is the professional identity of the pedagogue in the school and extracurricular fields? The objective of this work was to discuss the professional identity of the pedagogue in the school and extracurricular fields. To achieve this, exploratory bibliographic research with a qualitative approach was used. Thus, professional identity in the contemporary context is a concept open to (re)definitions, due to the complexity of society and social relations. This term refers to the knowledge, skills, competencies, and practices mobilized by each profession, differentiating it from others that exist. In the case of a pedagogue, their identity extends both to the school, as a teacher, principal, and pedagogical coordinator, and to extracurricular activities, carrying out pedagogical-related tasks. Therefore, a pedagogue differs from a teacher because they can work beyond the school, contributing to the human and emancipatory development of individuals in different social spaces.